Simulating defects in brick masonry panels subjected to compressive loads. (15th July 2022) - Gregori, Amedeo; Mercuri, Micaela; Angiolilli, Michele; Pathirage, Madura
Abstract: Although widespread in civil engineering construction, brick masonry walls usually designed to resist only gravity loads are known to be vulnerable structural elements with respect to seismic loads. They are generally made of units (bricks, stones or concrete blocks) and mortar joints and are by definition non-homogeneous and composite structures. The mechanical behavior of brick masonry has been studied extensively in the past decades both experimentally and by means of numerical simulations, considering the complex interaction between units and the surrounding mortar. One major aspect of the structural vulnerability of masonry panels, not well explored in the current literature, is the presence of geometrical and material defects accidentally introduced within the masonry panel during the construction process. Accounting for these defects by performing experimental campaigns is very difficult under the point of view of the replicability and, also, it is a costly and time-consuming activity. This manuscript deals with the modeling of the compressive behavior of brick masonry panels accounting for the presence of geometrical and material defects. For this purpose, a micro-modeling approach is proposed where brick units, mortar joints, and unit-mortar interfaces are simulated explicitly and the nonlinear behavior of the constituent materials is taken into account. The model was first validated on a large set of experimental data by predicting the overall panels' elastic behavior and bearing capacity of four different types of brick wall geometries. Next, geometrical and material defects were introduced in the model including: (i) the absence or the ineffectiveness or vertical mortar joints, (ii) the variability in the thickness of horizontal mortar joints and (iii) the inherent random distribution of bricks and mortar mechanical properties. Numerical results show that the quality of vertical joints defects does not significantly affect the mechanical response of masonry panels in compression, whereas the horizontal mortar joint defects can reduce the masonry compressive strength up to about 35%. In terms of material defects, the variability in compressive strength of brick units alone was found not to alter the mechanical behavior of the panels. On the other hand, both the overall strength and ductility of the masonry walls are appreciably affected when a not uniform distribution of the material properties are considered simultaneously in brick units and mortar joints. Highlights: Defects of horizontal mortar joints influence masonry's compressive behavior. The compressive strength decreases up to about 35% respect to the benchmark case. Brick strength variability affects about 5% the compressive response of the panel. Variable brick strength and non-homogeneous mortar influence the compressive behavior. The compressive strength is about 13% lower than the no-defect case.